The Relationship between Tumor Size and Carcinoembryonic Antigen (CEA) Levels in Stage IV Colorectal Adenocarcinoma Patients at Dr. Moewardi Hospital, Indonesia - Eri, Rakhmawati Susetyaning; Kusumaningrum, Sulistyani; Widiastuti, Widiastuti; Wujoso, Hari; Adnyana, Ida Bagus Budhi Surya; Putro, Prasetyo Sarwono (Indonesian Journal of Medicine, 2021)
Background: Colorectal adenocarcinoma is one of the most common types of colorectal cancer based on histopathology, accounting for about 10% of cancer cases diagnosed worldwide each year. Tumor size and levels of carcinoembryonic antigen (CEA) are used to determine the presence and evaluation of colorectal cancer. However, studies on the correlation between the size of colorectal cancer based on CT scan abdominal with contrast and the CEA levels are still very minimal in the Indonesian population. This study aimed to analyze the relationship between tumor size examined by abdominal CT scan with contrast and carcinoembryonic antigen (CEA) levels in stage IV colorectal adenocarcinoma patients.Subjects and Method: A cross-sectional study was conducted at the radiology department, Dr. Moewardi hospital, Surakarta, from February 2021 to July 2021. A total of 40 patients with stage IV colorectal adenocarcinoma were selected in this study. The patient already had the examination results of blood CEA levels and performed an abdominal CT scan with contrast. The dependent variable was blood CEA levels. The independent variable was tumor size. Data were collected from medical records and analyzed by the Spearman test.Results: There was a positive and significant relationship between tumor size and CEA levels (r= 0.47; p= 0.003).Conclusion: Tumor size is positively correlated to blood CEA levels in patients with stage IV colorectal adenocarcinoma.Keywords: colorectal adenocarcinoma, contrast abdominal CT scan, carcinoembryonic antigen (CEA).Correspondence: Sulistyani Kusumaningrum. Department of Radiology Dr. Moewardi Hospital/ Faculty of Medicine of Universitas Sebelas Maret, Surakarta. Email: sulistyani_sprad@staff.uns.ac.idIndonesian Journal of Medicine (2021), 06(03): 285-290https://doi.org/10.26911/theijmed.2021.06.03.05